Partitioning of the pesticide trifluralin between dissolved organic matter and water using automated SPME-GC/MS - Caupos, E.; Touffet, A.; Mazellier, P.; Croue, Jean-Philippe (Springer Verlag, 2015)
Solid-phase microextraction (SPME) was used to determine the equilibrium association constant for a pesticide, trifluralin (TFR), with dissolved organic matter (DOM). After optimization of the SPME method for the analysis of TFR, partition coefficients (KDOM) with three different sources of DOM were determined in buffered solutions at pH 7. Commercial humic acids and DOM fractions isolated from two surface waters were used. The values of log KDOM varied from 4.3 to 5.8, depending on the nature of the organic material. A good correlation was established between log KDOM and DOM properties (as measured with the H/O atomic ratio and UV absorbance), in agreement with literature data. This is consistent with the effect of polarity and aromaticity for governing DOM-pollutant associations, regardless of the origin of DOM. This association phenomenon is relevant to better understand the behavior of pesticides in the environment since it controls part of pesticide leaching and fate in aquatic systems.